THE ROLE OF ARTIFICIAL INTELLIGENCE IN FOREIGN LANGUAGE TEACHING: THEORETICAL FOUNDATIONS AND PRACTICAL APPLICATION (SCIENCE TIME JOURNAL, 2026)
Artificial Intelligence (AI) is increasingly reshaping the field of foreign language education by offering adaptive, interactive, and personalized learning environments. This paper explores the theoretical foundations and practical applications of AI in language teaching. Drawing on constructivist and learner-centered approaches, the study highlights how AI technologies such as intelligent tutoring systems, chatbots, speech recognition, and automated grammar tools enhance motivation, accessibility, and efficiency in language acquisition. A qualitative literature review was conducted to analyze recent research on AI-driven language learning. Findings suggest that AI supports personalized instruction, reduces learner anxiety, and provides real-time feedback, while also raising concerns about cultural depth and learner dependency. The discussion emphasizes the need for responsible integration of AI, ensuring that technological innovation complements rather than replaces the irreplaceable human role of teachers. The paper concludes that AI holds significant potential to democratize language education and foster lifelong learning, provided its implementation remains guided by sound pedagogical principles.